Emplacing India's "medicities". (November 2016) - Murray, Susan F.; Bisht, Ramila; Pitchforth, Emma
Abstract: Plans for 'medicities', announced in the Indian press from 2007 onwards, were to provide large scale 'one-stop-shops' of super-speciality medical services supplemented by diagnostics, education, research facilities, and other aspects of healthcare and lifestyle consumption. Placing this phenomenon within the recent domestic and global political economy of health, we then draw on recent research literatures on place and health to offer an analysis of the narration of these new healthcare places given in promotional texts from press media, official documents and marketing materials. We consider the implications of such analytic undertakings for the understanding of the evolving landscapes of contemporary health care in middle-income countries, and end with some reflections on the tensions now appearing in the medicity model.